2005
DOI: 10.1590/s0103-50532005000700012
|View full text |Cite
|
Sign up to set email alerts
|

Thallium trinitrate-mediated ring contraction of 1,2-dihydronaphthalenes: the effect of electron-donating and electron-withdrawing groups

Abstract: A oxidação de uma série de 1,2-diidronaftalenos, substituídos no anel aromático, foi investigada com trinitrato de tálio (TTN) em metanol ou em trimetilortoformiato (TMOF) como solvente. Em todos os casos, indanos foram formados, embora o rendimento tenha variado de excelente a baixo, dependendo da estrutura do substrato. A presença de um grupo doador de elétrons no substrato favorece o rearranjo, enquanto que uma quantidade significativa de derivados glicólicos, bem como naftalenos, foi obtida na oxidação de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…A substituent in the aromatic ring can alter the migratory aptitude of the migrating carbon, which may influence the yield of the rearrangement product. For example, a correlation between yield of the product and migratory aptitude was noted by us in Tl(III)-mediated ring contraction of 1,2-di-hydronaphthalenes [43]. Thus, we investigated the ring expansion of 3 with different groups in the aromatic ring.…”
Section: Resultsmentioning
confidence: 98%
“…A substituent in the aromatic ring can alter the migratory aptitude of the migrating carbon, which may influence the yield of the rearrangement product. For example, a correlation between yield of the product and migratory aptitude was noted by us in Tl(III)-mediated ring contraction of 1,2-di-hydronaphthalenes [43]. Thus, we investigated the ring expansion of 3 with different groups in the aromatic ring.…”
Section: Resultsmentioning
confidence: 98%
“…When the dehydration was performed with H 3 PO 4 , the 1,2-dihydronaphthalene was isolated in good yield only on a small scale. Using more than 1 mmol of starting material 6 , the formation of a complex mixture was observed [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of 1,2-dihydronaphthalene 5 with iodine(III) [ 20 , 22 , 31 , 32 , 33 , 34 ] or with thallium(III) [ 30 , 31 , 33 , 35 , 36 , 37 , 38 , 39 , 40 ] in MeOH furnished the indane 4 , the naphthalene 7 and the addition product 8 , depending on the reaction conditions ( Table 1 ). With 0.9 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 Our research group has investigated approaches to obtain indans from 1,2-dihydronaphthalenes, using a thallium(III)-promoted ring contraction reaction. [4][5][6][7][8][9] During these studies, we found that a side chain at the double bond has a strong influence in the reaction pathway. 5 The treatment of 1,2-dihydronaphthalenes bearing a β,γ-unsaturated carboxylic acid unit, such as 1, with thallium triacetate (TTA) gave a mixture of the isomeric allylic acetates 2 and 3, which are produced through an oxidative decarboxylation process (Scheme 1).…”
Section: Introductionmentioning
confidence: 96%
“…4,6 The homoallylic alcohols 7 were efficiently obtained in three steps from 1-tetralones, through the β,γ-unsaturated esters 6. We then realized that these esters would also be interesting substrates for thallium(III)-promoted ring contraction reactions, because the indans products of this transformation (9), would bear a β-keto ester unit, which is a valuable moiety for further functionalization 11 (Scheme 3).…”
Section: Introductionmentioning
confidence: 99%